Pengaruh Pengalaman Kerja, Kompetensi dan Integritas Auditor Terhadap Kualitas Hasil Audit - Cahyadi Wiranata Kusuma, Made; Eka Damayanthi, I Gst Ayu (E-Jurnal Akuntansi; Vol 30 No 9 (2020)DO - 10.24843/EJA.2020.v30.i09.p18, 2020)
The Asean Economic Community (MEA) is one of the triggers of economic development in Indonesia. Many companies in Indonesia are going public. So it is necessary for financial statements that are honest, reasonable and do not mislead the wearer. One of the policies that can be taken is by auditing the financial statements by the auditor. This study aims to determine the effect of work experience, competence, and auditor integrity on the audit quality. The object of the research is the quality of the audit results in KAP in Bali. The sampling technique was purposive sampling, namely the technique of determining samples with certain considerations. The sample was 65 auditors with 42 statements. Based on the results of the analysis, Work Experience has a negative influence on the Audit Quality, Competence has a positive influence on the Audit Quality, and auditor Integrity has a positive influence on the Audit Quality. Keywords: Work Experience; Competence; and Auditor Integrity.